Splenic Complications of Babesia microti Infection in Humans: A Systematic Review - Igor Dumic; Cristian Madrid; Libardo Rueda Prada; Charles W. Nordstrom; Pahnwat Tonya Taweesedt; Poornima Ramanan (Canadian Journal of Infectious Diseases and Medical Microbiology)
Splenic complications of acute Babesia microti infection include splenomegaly, splenic infarct, and splenic rupture. These complications are relatively rarely reported, and the aim of this research was to synthetize data on this topic according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using the PubMed database. In this review, we find that unlike other severe complications of babesiosis, splenic infarct and rupture occur in younger and immunocompetent patients, and they do not correlate with parasitemia level. Furthermore, admission hemoglobin of 10 mg/dl or less, platelet count of 50 × 10⁹/L or less, presence of hemodynamic instability, and splenic rupture were associated independently with an increased risk of requiring splenectomy. As babesiosis is an emerging tick-borne zoonosis, we hope that this review will help to raise awareness among clinicians regarding this rare but potentially life-threatening complication.